“That Was the Biggest Help”: The Importance of Familial Support for Science, Technology, Engineering, and Math Community College Students - Bueno, Elia H.; Velasquez, Selena M.; Deil-Amen, Regina; Jones, Candace (Frontiers in Education, 2022)
This study reveals the informal instrumental and socio-emotional support that non-traditional (e.g., Latinx, Black, Indigenous, lower-income, and first-generation) college students receive from family members that combat experiences of marginalization and contribute towards their self-efficacy. Family support can be particularly important for underrepresented undergraduate Science, Technology, Engineering, and Math (STEM) students who are at higher risks of dropping out of their program and experience lower levels of success indicators (e.g., sense of belonging, self-concept, and STEM identity) compared to their white and Asian peers. Utilizing a phenomenological approach, we used open-ended questions during focus groups with community college transfer students to gain their experiences with challenges and feelings of belonging in college and STEM. We apply the funds of knowledge framework to investigate the value family support holds for students in navigating STEM challenges and expand the definition of family to include romantic partners and extended family.